3D Reconstruction and Visualization of Tissue Structure and Elasticity Using Robot-Assisted Ultrasound and Shear Wave Elastography Imaging * - Furman, Anna; Karmann, Niklas; Jung, Alexander; Steinberger, Nadine; Leher, Irina; Hartwich, Reinhold; Walter, Jonas; Franke, Jörg; Martin, Sina (2025 47th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC), 2025)
Tissue elasticity is a critical component of medical diagnostics, serving as a key indicator for tumor detection and pain assessment. Moreover, understanding tissue stiffness is essential for the precise fitting of prostheses. Conventional imaging techniques such as Magnetic Resonance Imaging or Computed Tomography (CT), besides being costly, fall short in accurately measuring tissue stiffness, highlighting the need of innovative approaches like shear wave elastography (SWE). The three-dimensional (3D) reconstruction for SWE images has the potential to provide a simplified visual interpretation of tissue properties. However, the acquisition of high-quality, meaningful images and an accurate 3D reconstruction necessitates the precise positioning of the transducer and the controlled application of pressure. Robotic assistance offers a solution to these challenges by ensuring repeatability and enabling detailed 3D imaging, thereby further improving the understanding of tissue structure. Building up on our prior work with conventional ultrasound (US), this study advances our methodology by adding SWE in an experiment conducted on a multi-layered silicone phantom. This not only provides an overview of the phantom’s structure but also illustrates the stiffness distribution across the phantom. Additionally, the study includes a comparison with clinical CT imaging, demonstrating the benefits of 3D US and SWE. Overall, this research demonstrates the viability of incorporating SWE into robot-assisted systems and the reconstruction of 3D SWE data. These findings lay the foundation for future advancements in tissue characterization.Clinical Relevance— Precise 3D visualization of tissue structure and elasticity improves diagnostic accuracy for conditions such as tumors and chronic diseases. In addition, this technique has the potential to enhance the customization of prostheses, thereby improving patient quality of lif